In vitro safety assessments and antimicrobial activities of Lactobacillus rhamnosus strains isolated from a fermented mare's milk. (1st August 2016) - Aryantini, Ni Putu Desy; Yamasaki, Eiki; Kurazono, Hisao; Sujaya, I Nengah; Urashima, Tadasu; Fukuda, Kenji
Abstract: Safety and probiotic characteristics such as antimicrobial activities of three Lactobacillus rhamnosus strains, FSMM15, FSMM22 and FSMM26, previously isolated as potential probiotics from fermented mare's milk were investigated. The three FSMM strains were susceptible to ampicillin, gentamycin, kanamycin, streptomycin, tetracycline and chloramphenicol, whereas they were resistant to erythromycin (minimal inhibitory concentration (MIC) = 4−8 µg/mL) and clindamycin (MIC = 4 µg/mL); bioconversion of bile salts, hemolytic activity and mucin degradation activity were negative; enzymatic activities of α‐chymotrypsin and β‐glucosidase were detected, but those of α‐galactosidase, β‐glucuronidase and N ‐acetyl‐β‐glucosaminidase, were undetectable. Among the strains, strain FSMM15 was chosen as a safer probiotic candidate due mainly to the lack of plasminogen binding ability. Despite lower acid production of strain FSMM15 than others, its cell‐free culture supernatant inhibited growths of Salmonella Typhimurium LT‐2, Shigella sonnei, Listeria monocytogenes, and Escherichia coli O157 with comparable levels of ampicillin, suggesting a favorable aspect of strain FSMM15 as a probiotic strain.